Implementasi Metode RUP dalam Pengembangan Sistem Informasi Kepegawaian PT Jalur Sutra - Agethie, Muhammad Trisna; Rachmadi, Muhammad (Universitas Multi Data Palembang, 2025)
The purpose of creating a staffing information system at PT Jalur Sutra that has been made is to assist the admin section in viewing data management related to employment such as employee data, leave data, mutation data, demotion data, promotion data, layoff data, reward punishment data and data employee attendance record. In addition to the admin section, this staffing information system can also assist employees in carrying out employee attendance independently. Making this application is made with supporting applications such as Visual Studio Code, Android Studio, XAMPP, MySQL and the Laravel Framework. The system development methodology used is the RUP (Rational Unified Process) methodology by observing the running system, collecting data in the form of interviews and literature studies, conducting analysis, carrying out the final design and implementation to be used by PT Jalur Sutra. The result of making this application is that it can help the admin section in viewing staffing management data and for the employee section in carrying out employee attendance independently.